Advances in conservative treatment of urinary incontinence - Bujnowska-Fedak, Maria Magdalena; Steciwko, Andrzej (Przewodnik Lekarza/Guide for GPs, 2007)
There are more and more new methods in the treatment of urinary incontinence. Conservative therapy is the first choice treatment in patients with urinary incontinence. Beside the selective anticholinergic drugs solifenacin and darifenacin, there is duloxetine, the first medicine with the highest reference level registered in the treatment of stress urinary incontinence. A lot of other drugs are still in the experimental phase. Among physiotherapeutic methods the use of extracorporeal magnetic stimulation seems to be promising. It is beneficial to combine a few different methods of treatment. The aim of the paper is to present the current knowledge and opinions on conservative treatment of patients with urinary incontinence.